Engineered porphyrin loaded core-shell nanoparticles for selective sonodynamic anticancer treatment. (December 2015) - Varchi, Greta; Foglietta, Federica; Canaparo, Roberto; Ballestri, Marco; Arena, Francesca; Sotgiu, Giovanna; Guerrini, Andrea; Nanni, Cristina; Cicoria, Gianfranco; Cravotto, Giancarlo; Fanti, Stefano; Serpe, Loredana
Aim: Porphyrin-loaded core-shell nanoparticles have been engineered for use as in vivo sonosensitizing systems, radio-tracers or magnetic resonance (MR) imaging agents, which may be suitable for the selective treatment of solid tumors and imaging analyses.Materials & methods: Polymethyl methacrylate nanoparticles (PMMANPs) have been either loaded with meso-tetrakis (4-sulphonatophenyl) porphyrin (TPPS) for sonodynamic anticancer treatment, with 64 Cu-TPPS for positron emission tomography biodistribution studies or with Mn(III)-TPPS for MR tumor accumulation evaluation.Results: PMMANPs are easily functionalized with negatively charged molecules and show favorable biodistribution. In vivo TPPS-PMMANPs have demonstrated shock wave responsiveness in a Mat B III syngeneic rat breast cancer model as measured by MR analyses of pre- and post-treatment tumor volumes.Conclusion: TPPS-PMMANPs are a multimodal system which can efficiently induce in vivo sonodynamic anticancer activity.